RHIZOSPHERE COMPETENCE OF THREE ENTOMOPATHOGENIC FUNGI IN RELATION TO HOST PLANT AND INTER-SPECIFIC INTERACTION - N. Geetha; D. Nithya; K. Hari; M. Preseetha; K. Subadra Bai; G. Santhalakshmi (Journal of Sugarcane Research, 2020)
Three commonly used entomopathogenic fungi (EPF) in sugarcane ecosystem, namely Beauveria bassiana (Balsamo) Vuillemin, Beauveria brongniartii (Saccardo) Petch and Metarhizium anisopliae (Metchnikoff) Sorokin were assessed for their ability to sustain themselves in the rhizosphere in the presence or absence of competition with other fungi, either native or inoculated. In the first of two studies, the inoculated EPFs applied singly were recovered from rhizosphere of five dicots and five monocot crops from sterilized soil as well as unsterilized soil. In the second study, the efficacy of the EPF to survive in the rhizosphere of sugarcane with or without competition from either of the other two EPF or two nematophilic fungi or two antagonistic fungi or two soil saprophytes or sugarcane wilt pathogen Fusarium sp. in sterilized or unsterilized soil was estimated. Results of the first study indicated that in sterilized soil medium, the rhizosphere of okra (82.2%) was the most favourable for survival of EPF which was comparable with most monocots tested. Beauveria bassiana (75.0%) and M. anisopliae (79.0%) were more efficient than B. brongniartii (66.3%) regardless of plant species. The lowest spore harvest was from larvae  rapped in rhizosphere of brinjal (3.88 x 107/larva) followed by that from cotton rhizosphere (5.55x107/larva). In the second study, in sugarcane rhizosphere in sterilized medium, the mortality of the larvae caused by B. bassiana was synergized by M. anisopliae (96.7%) and significantly higher than all other treatments. In case of B. brongniartii, mortality rates were most affected by fungal antagonists and Fusarium sp. (50.0-53.3%) while M. anisopliae was affected by Trichoderma harzianum (53.3%). Sporulation of Beauveria spp. was consistently affected by Penicillium sp./Aspergillus sp. while most species were competitive with M. anisopliae. In both the studies, only M. anisopliae spores could be recovered from unsterilized soil.